Equação do segundo grau : aspectos históricos e contemporâneos - Chaves, Ezequiel Silva (2018)
In this work we present an analysis of the current problems concerning the equations of the second degree equations and quadratic functions. This is an issue that is addressed at the end of elementary school and beginning of high school. It can be seen that since ancient times the quadratic equation and later the quadratic functions have attracted the attention of several peoples, considering that approximately 3500 years have passed (from the Egyptians to Vi`ete) to arrive at a quadratic formula for the same. The objective of this work is to make a historical rescue of problems involving the quadratic equation in several peoples, and to explore the contemporaneous aspects of the same, particularly those contained in didactic books, supplementary educational materials among others, verifying which relationships exist between the problems which are addressed in the classroom with situations of the day by day of the student.